Graffiti for the City or the City for Graffiti? Legitimacy of Graffiti in the Historical Center of Saint-Petersburg - Ivan E. Safonov; Ekaterina V. Shapiro; Ekaterina M. Lukina; Sofia A. Shchepkina (Галактика медиа: журнал медиа исследований, 2022)
In contemporary society there are two contradictory points of view concerning graffiti: it is vandalism; it is art. In the cities graffiti is treated ambiguously: negatively, quietly or with interest and approval. The reasons for this may be both in citizens’ tastes and in the characteristics of the graffiti itself. Why do citizens consider some graffiti acceptable and some not? This work deals with the research of the legitimacy of the graffiti in the historical center of Saint-Petersburg. The purpose of the research is to reveal the foundations of the legitimacy of illegal graffiti in the historical center.